Positioning and stiffening of an articulated/continuum manipulator for implant delivery in minimally invasive surgery. Issue 2 (3rd February 2020) - Tamadon, Izadyar; Huan, Yu; de Groot, Antonius G.; Menciassi, Arianna; Sinibaldi, Edoardo
Abstract: Background: Hollow, bendable manipulators can advance implant delivery in minimally invasive surgery, by circumventing the drawbacks of straight‐line delivery and fostering single‐port approaches. Variable stiffness manipulators are sought to be safe and effective. Methods: We designed and experimentally assessed a cable‐driven articulated/continuum manipulator, devised for cardiac valve delivery. Positioning and stiffening were teleoperated, based on cable shortening. Stiffening was parameterized by using the leading tension (LT, ie, tension of the cables driving bending). We assessed positioning (repeatability/reversibility along eight/two bending directions) and stiffening (eight bent configurations). Results: We achieved good repeatability and reversibility (mean errors <1% and 1.5%, respectively, of the workspace characteristic length). Stiffening was effective (up to 9‐fold increase, depending on pose). Stiffening was linearly correlated ( R 2 = 0.92) with LT for all the considered configurations. Conclusion: We accurately positioned and effectively stiffened the manipulator in several bent configurations. The proposed stiffness modulation strategy can be extended to other manipulators.